Operational constraints of equity financed budget deficit in interest-free economy. (2017) - Onour, Ibrahim A.
This paper investigate conditions under which equity funds can be a sustainable source of budget deficit financing in an interest free economy. Our findings show equity fund can be a sustainable source of deficit financing when the rate of return on equity fund exceeds the budget deficit expansion rate. This is because when the budget deficit expansion rate exceeds the rate of return on equity fund, the return per unit of the equity fund declines over time as more investment units need to be issued to meet the expanding budget deficit. Our results also show that to maintain stable demand for equity fund units, it is essential to maintain the size of the fund at a fixed level, and ensure that the rate of return on those units exceed the rate of cost of capital financing.